LEGAL CONSEQUENCES OF BREACH IN INVESTMENT AGREEMENTS WITHOUT NOTARY DEED BASED ON ISLAMIC LAW PERSPECTIVE - Sulmarty, Sulmarty; Saleh, Moh. (JURNAL ILMU SYARIAH, 2022)
Not all investment agreements are made before a notary, so that agreement does not have strong enough evidence, so when one party commits a default, the other party does not have sufficient evidence to prosecute the party committing the default before the law. The purpose of this study is to analyze the validity of investment agreements without a notary deed and the legal consequences of default in investment agreements without a notary deed. This research is a normative legal research technique. This research used descriptive, interpretation, evaluation, and argumentation techniques to analyze legal material. Akad (contract) is a bond that occurs between two parties, one states ijab and the second states qabul, which then creates legal consequences, namely the emergence of rights and obligations between the two parties. This ijab and qabul show that both parties have voluntarily entered into an agreement that made must be in accordance with the Shari'a. The agreement made not before a notary is still valid, as long as it has fulfilled the legal requirements of the agreement stated in Article 1320 of the Civil Code and as long as no law stipulates that the agreement to be made must be in writing. Legal consequences of the default, the debtor is required to pay compensation for the losses suffered by the creditor, if the engagement is reciprocal, the creditor can demand termination or cancellation of the engagement through the court, the engagement to provide something, the risk of switching to the debtor since the default, the debtor is required to fulfill the engagement if it can still be made or cancellation, accompaniedby payment of compensation, and the debtor obliged to pay court fees if brought before a district court and debtor found guilty.